2000
DOI: 10.1055/s-2000-8454
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of the Factor VII-Dependent Coagulation Pathway: Rationale for the Effectiveness of Recombinant Factor VIIa in Refractory Bleeding Disorders

Abstract: We have explored the molecular basis of the clinical therapeutic effect of factor VIIa in hemophilia A using empirical reconstituted in vitro thrombin generation models. Tissue factor acts as a receptor and activator of preexistent but virtually inactive two-chain plasma factor VIIa. However, most of the factor VII circulates as a single-chain inactive zymogen (10 nM) and a trace (approximately 10-100 pM) circulates in the active two-chain form. Empirical reconstitution (purified factors VIIa, X, IX, VIII, V, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…It acts by directly binding to tissue factor to activate thrombin generation, bypassing much of the cascade of coagulation factors (14). There may also be an independent effect on activated platelet function (15).…”
Section: Discussionmentioning
confidence: 99%
“…It acts by directly binding to tissue factor to activate thrombin generation, bypassing much of the cascade of coagulation factors (14). There may also be an independent effect on activated platelet function (15).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Mann and colleagues [23][24][25][26] hold the view that the mechanism of action of factor VIIa is dominated by the tissue factor-mediated activity with only a minimal, if any, contribution from TF-independent fVIIa activity. In studies using TF incorporated into lipid vesicles, van't Veer et al observed that fVIIa overcomes the inhibitory effect of zymogen fVII on thrombin generation.…”
Section: Mechanism Of Action Of Factor Viiamentioning
confidence: 99%
“…In studies using TF incorporated into lipid vesicles, van't Veer et al observed that fVIIa overcomes the inhibitory effect of zymogen fVII on thrombin generation. 23,24 While the influence of rfVIIa is dependent on TF, Butenas et al observed that phospholipids or platelets substantially increase the hemostatic potential of rfVIIa. 25,26 Lisman and De Groot have recently analyzed the alternative mechanisms of action of rfVIIa.…”
Section: Mechanism Of Action Of Factor Viiamentioning
confidence: 99%
“…4,5 However, different independent experiments have shown that the effect of rFVIIa can proceed via TF-dependent 3,6 as well as TF-independent 7-9 pathways, and it has been postulated that both mechanisms are operative in vivo. 10 Although the mechanisms through which rFVIIa exerts its activity have been studied extensively, there are still some unresolved questions.…”
Section: Introductionmentioning
confidence: 99%